2002
DOI: 10.1007/s00464-001-9223-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life for patients with gastroesophageal reflux disease 2 years after laparoscopic fundoplication

Abstract: The initial phase of learning does not affect the improvement of HRQL observed after laparoscopic antireflux surgery, which is consistent with durable relief of symptoms and endoscopic healing. Evaluation of HRQL should be added to, and probably could replace in most cases, the objective postoperative testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 17 publications
8
24
0
Order By: Relevance
“…However, there have not been any reports with a high evidence level. One paper reported that the clinical outcome of antireflux surgery is influenced by the learning curve [153], and other reports have found no significant differences [154][155][156][157].…”
Section: (4) Enteric Infectionmentioning
confidence: 99%
“…However, there have not been any reports with a high evidence level. One paper reported that the clinical outcome of antireflux surgery is influenced by the learning curve [153], and other reports have found no significant differences [154][155][156][157].…”
Section: (4) Enteric Infectionmentioning
confidence: 99%
“…The learning phase for laparoscopic anti-reflux surgery is reported to be 15-20 cases and studies have suggested that surgeons seek experienced supervision during their learning period to minimize adverse outcome [26]. Also, good results have been reported by young surgeons after appropriate training in laparoscopy [28,29]. In our series, we experienced neither open conversion nor surgical mortality.…”
Section: Gastroesophageal Reflux Disease (Gerd) Is a Commonmentioning
confidence: 73%
“…Most important are the reports on the improvement in quality of life of patients operated on by laparoscopic Nissen fundoplication compared to the restricted quality of life, prior to surgery, under PPI treatment. Several studies have shown that quality of life can be elevated and brought to normal levels in patients with gastro-oesophageal reflux disease when patients are well selected for surgery and a fundoplication is performed [38][39][40][41]. Quality of life can be significantly improved by laparoscopic Nissen repair in patients with reflux disease (Table 5).…”
Section: Resultsmentioning
confidence: 94%